Draf Laporan Publikasi Riset Potensi Pasar Analisis Strategi Pasar Pada Produk Scarlett - Norma Puspitasari; Alvina Novanka; Syamsul Hidayat (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research explains the importance of cosmetics as a primary need, especially for women, in line with public awareness about self-care. Research methods include quantitative and qualitative approaches using questionnaires, observations and interviews. .The research results are expected to provide in-depth insight into market conditions, growth opportunities and challenges faced by Scarlett Whitening products